2021
DOI: 10.1111/hsc.13276
|View full text |Cite
|
Sign up to set email alerts
|

Trans intracommunity support & knowledge sharing in the United States & Canada: A scoping literature review

Abstract: Despite often facing multiple layers of oppression, some trans individuals are buffered by protective factors, adaptive coping, privileged social identities or through supporting one another within the transgender (i.e. trans) community. This support takes many forms, including knowledge or skill sharing, sharing medical referrals and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 54 publications
1
10
0
Order By: Relevance
“…Relatedly, participants sourced peer-based medical advice and support from online detransition networks to address unmet clinical care. This is consistent with existing research showing transgender people seek and provide peer-based mental health support and engage in peer-to-peer health information sharing …”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Relatedly, participants sourced peer-based medical advice and support from online detransition networks to address unmet clinical care. This is consistent with existing research showing transgender people seek and provide peer-based mental health support and engage in peer-to-peer health information sharing …”
Section: Discussionsupporting
confidence: 90%
“…This is consistent with existing research showing transgender people seek and provide peer-based mental health support 37 and engage in peer-to-peer health information sharing. 38 …”
Section: Discussionmentioning
confidence: 99%
“…TikTok also provides a platform for health care providers and researchers who specialize in gender-affirming medicine to educate other clinicians and policy makers. Reflecting contemporary collaborative knowledge coproduction [ 42 ], trans communities are digitally well-connected and are active in peer-to-peer information sharing, support, and intracommunity education on the web [ 22 , 49 , 50 ]. This creates optimal conditions for community-engaged research and digital knowledge exchange between researchers, health care providers, and trans health care users.…”
Section: Community-engaged Knowledge Mobilization and Trans Peer-to-peer Information Sharingmentioning
confidence: 99%
“…A 2021 scoping review found that social media and web-based communities were sources of both peer-based support and resilience for trans people, which in turn could buffer poor mental health outcomes experienced by this population [ 49 ]. Another 2021 scoping review identified advocacy and education as prominent themes of trans peer-to-peer information sharing and support [ 22 ]. Lupton [ 31 ] specifically recommends examining how TikTok and other social media platforms are used for health-related content creation and peer-to-peer sharing among young people.…”
Section: Community-engaged Knowledge Mobilization and Trans Peer-to-peer Information Sharingmentioning
confidence: 99%
See 1 more Smart Citation